Existence and uniqueness of continuous solution of mixed type integra equations in cone metric space - Tidke, HL; Aage, CT; Salunke, JN (Kathmandu University Journal of Science Engineering and Technology, 2011)
In this paper we investigate the existence and uniqueness for Volterra-Fredholm type integral equations in cone metric spaces. The result is obtained by using the some extensions of Banach's contraction principle in complete cone metric space.